Exponential Stability of Linear Discrete Systems with Multiple Delays - J. Baštinec; H. Demchenko; J. Diblík; D. Ya. Khusainov (Discrete Dynamics in Nature and Society)
The paper investigates the exponential stability and exponential estimate of the norms of solutions to a linear system of difference equations with multiple delays xk+1=Axk+∑i=1sBixk-mi, k=0,1,…, where s∈N, A and Bi are square matrices, and mi∈N. New criterion for exponential stability is proved by the Lyapunov method. An estimate of the norm of solutions is given as well and relations to the well-known results are discussed.